Population genomics of the filarial nematode parasite Wuchereria bancrofti from mosquitoes. Issue 7 (15th March 2016) - Small, Scott T.; Reimer, Lisa J.; Tisch, Daniel J.; King, Christopher L.; Christensen, Bruce M.; Siba, Peter M.; Kazura, James W.; Serre, David; Zimmerman, Peter A.
Abstract: Wuchereria bancrofti is a parasitic nematode and the primary cause of lymphatic filariasis – a disease specific to humans. W. bancrofti currently infects over 90 million people throughout the tropics and has been acknowledged by the world health organization as a vulnerable parasite. Current research has focused primarily on the clinical manifestations of disease and little is known about the evolutionary history of W. bancrofti . To improve upon knowledge of the evolutionary history of W. bancrofti, we whole genome sequenced 13 W. bancrofti larvae. We circumvent many of the difficulties of multiple infections by sampling larvae directly from mosquitoes that were experimentally inoculated with infected blood. To begin, we used whole genome data to reconstruct the historical population size. Our results support a history of fluctuating population sizes that can be correlated with human migration and fluctuating mosquito abundances. Next, we reconstructed the putative pedigree of W. bancrofti worms within an infection using the kinship coefficient. We deduced that there are full‐sib and half‐sib relationships residing within the same larval cohort. Through combined analysis of the mitochondrial and nuclear genomes we concluded that this is likely a results of polyandrous mating, the first time reported for W. bancrofti . Lastly, we scanned the genomes for signatures of natural selection. Annotation of putative selected regions identified proteins that may have aided in a parasitic life style or may have evolved to protect against current drug treatments. We discuss our results in the greater context of understanding the biology of an animal with a unique life history and ecology.